Frontiers and hotspots of 18F-FDG PET/CT radiomics: A bibliometric analysis of the published literature - Liu, Xinghai; Hu, Xianwen; Yu, Xiao; Li, Pujiao; Gu, Cheng; Liu, Guosheng; Wu, Yan; Li, Dandan; Wang, Pan; Cai, Jiong (Frontiers in Oncology, 2022)
Objective: To illustrate the knowledge hotspots and cutting-edge research trends of 18F-FDG PET/CT radiomics, the knowledge structure of which was systematically explored and the visualization map was analyzed. Methods: Studies related to 18F-FDG PET/CT radiomics from 2013 to 2021 were identified and selected from the Web of Science Core Collection (WoSCC) using retrieval formula based on an interview. The bibliometric approach was performed mostly by CiteSpace 5.8.R3. We used the software to construct intellectual structures (including publication output, collaborations and co-citation research, burst analysis, etc.). Performance and relevance of countries, institutions, authors, and journals were measured by knowledge maps. Results: A total of 457 documents and their references were analyzed. These papers were primarily published in USA (120), People’s republic of China (83). Memorial Sloan-Kettering Cancer Center and Southern Medical University are the most productive institutions with the frequency of 17. 18F-FDG PET/CT radiomics related literature was frequently published with high citation in European Journal of Nuclear Medicine and Molecular Imaging (IF9.236, 2020), Frontiers in Oncology (IF6.244, 2020), and Cancers (IF6.639, 2020). Further cluster profile of keywords and literature revealed that the research hotspots were primarily concentrated in the fields of image, textural feature, positron emission tomography, and the hot research disease is malignant tumor. Document co-citation analysis suggested that many scholars have a co-citation relationship in studies related to imaging biomarkers, texture analysis, and immunotherapy simultaneously. Burst detection suggests that adenocarcinoma studies are frontiers in 18F-FDG PET/CT radiomics, and the landmark literature put emphasis on the reproducibility of FDG-PET radiomics features. Conclusion: This bibliometric study provides references and suggestions for the development of related research in an updated perspective on 18F-FDG PET/CT radiomics. Above all, there will be a continuing growth of the number of public18F-FDG PET/CTations and citations. Secondly, the international research frontiers lie in applying 18F-FDG PET/CT radiomics into oncology research. To add more, new insights for researchers in future studies is to be adenocarcinoma related analyses. Besides, our findings also offer suggestions for scholars to give attention to maintain the reproducibility of 18F-FDG PET/CT radiomics features.